Toward an Understanding of Physical and Biological Properties of Corn-Based Whole Stillage, Thin Stillage, and Condensed Distillers Solubles and Changes Thereof During Storage - Rosentrater, Kurt A.; Yang, Lu (Frontiers in Energy Research, 2021)
The production of bio-based ethanol has been one of the fastest growing industries in the U.S. during the last decade. Thus, wider exploration of ethanol co-product uses is necessary in ethanol plant. Currently, process steams such as whole stillage, thin stillage and syrup are processed into distillers dried grains with solubles and fed to livestock. The storability of whole stillage, thin stillage and syrup influences the economic and energetic balances of fuel ethanol production. But there are few investigations of the shelf life for those products, or how to measure these quantities. The objectives of this research were to test physical and biological properties of whole stillage, thin stillage, and syrup, and determine storability and allowable shelf life for these materials as influenced by storage temperature levels. Using standard laboratory methods, several properties were determined, including moisture content, water activity, thermal properties (conductivity, resistivity, volumetric heat capacity, and diffusivity), color, mold development and CO2 production. Also, the separation processes due to settling were observed over 72 hours. The thin stillage and whole stillage had relative high average moisture contents of 92% (w.b.) and 87% (w.b.) respectively, and mean water activity of 0.99; the high water content marked samples easily susceptible to rapid spoilage. Time had a significant effect (P < 0.05) on properties of co-products. Both thin stillage and whole stillage samples got mold growth after 5 days incubation at 32oC. Thin stillage had the greatest separation rate in settling experiment. However, syrup had relative low average moisture content of 62% and average water activity of 0.92. No mold growth and settling separation happened in syrup samples. There were no evidence showing a linear relationship exists between Hunter L*, a* and b*, and mold growth. The Solvita® test showed that high-temperature treatment caused high CO2 production in all samples. The exponential models described the relationship between storage time (from 0 to 5 days at 25oC and 35oC) and CO2 concentration for three co-products.